U2 small nuclear RNA 3' end formation is directed by a critical internal structure distinct from the processing site. - Jacobson, M R (1993)
Mature U2 small nuclear RNA is generated by the removal of 11 to 12 nucleotides from the 3' end of the primary transcript. This pre-U2 RNA processing reaction takes place in the cytoplasm. In this study, the sequences and/or structures of pre-U2 RNA that are important for 3' processing have been examined in an in vitro system. The 7-methylguanosine cap, stem-loops I and II, the lariat branch site recognition sequence, the conserved Sm domain, and several other regions throughout the 5' end of U2 RNA have no apparent role in the 3' processing reaction. In fact, deletion of the entire first 104 nucleotides resulted in mini-pre-U2 RNAs which were efficiently processed. Similarly, deletion of the top two-thirds of stem-loop III or mutation of nucleotides in the loop of stem-loop IV had little effect on 3' processing. Most surprisingly, the precursor's 11- to 12-nucleotide 3' extension itself was of relatively little importance, since this sequence could be replaced with completely different sequences with only a minor effect on the 3' processing reaction. In contrast, we have defined a critical structure consisting of the bottom of stem III and the stem of stem-loop IV that is essential for 3' processing of pre-U2 RNA. Compensatory mutations which restore base pairing in this region resulted in normal 3' processing. Thus, although the U2 RNA processing activity recognizes the bottom of stem III and stem IV, the sequence of this critical region is much less important than its structure. These results, together with the surprising observation that the reaction is relatively indifferent to the sequence of the 11- to 12-nucleotide 3' extension itself, point to a 3' processing reaction of pre-U2 RNA that has sequence and structure requirements significantly different from those previously identified for pre-mRNA 3' processing.